Análisis de la concentración del mercado del sector agrícola en el Ecuador. Período 2015 – 2019. - Armijos Bravo, Manuela (Universidad Técnica de Machala, 2021)
This article studies the market competition of the agricultural sector in Ecuador, specifically of the subgroups corresponding to: A011 cultivation of non-perennial plants, and A012 cultivation of perennial plants of the International Standard Industrial Classification for the years 2015 to 2019. Consequently, the objective proposed in this study is to analyze the concentration of the agricultural sector market in Ecuador using concentration indicators, such as Cr4, Cr8, Herfindahl-Hirschman and the equivalent number, for which net sales have been used, in dollars, reported by the companies operating in this sector, information that has been provided by the Superintendency of Companies, Securities and Insurance of Ecuador for the years 2015-2019. As main conclusions, it can be mentioned that the market of the segments corresponding to the cultivation of non-perennial plants, and cultivation of perennial plants from 2015 to 2019 is not concentrated.
El presente artículo estudia la competencia del mercado del sector agrícola en el Ecuador, específicamente de los subgrupos correspondientes a: A011 cultivo de plantas no perennes, y A012 cultivo de plantas perennes de la clasificación Industrial Internacional Uniforme para los años 2015 al 2019. En consiguiente, el objetivo que se plantea en el presente estudio es el de analizar la concentración del mercado del sector agrícola en el Ecuador empleando indicadores de concentración, tales como Cr4, Cr8, Herfindahl-Hirschman y número equivalente, para lo cual se ha utilizado las ventas netas en dólares reportadas por las empresas que operan en este sector, información que ha sido proporcionada por la Superintendencia de Compañías, Valores y Seguros del Ecuador para los años 2015-2019. Como principales conclusiones se puede mencionar que el mercado de los segmentos correspondientes a los cultivos de plantas no perennes, y cultivo de plantas perennes del 2015 al 2019 no se encuentra concentrado.
Keywords: SECTOR AGRÍCOLA; INGRESOS POR VENTAS; CULTIVOS DE PLANTAS NO PERENNES; CULTIVO DE PLANTAS PERENNES